The ventilator and the vaccine: Necropolitics and fat in the Covid-19 pandemic - Deborah McPhail (Journal of Critical Public Health)
During the Covid-19 pandemic, the fat body was caught up in complicated logics of life and death in the North American context, where “obesity” was regarded as an “underlying condition” for greater risk of severe disease and death from Covid. As such, bodies with high Body Mass Indexes (BMIs) were refused Intensive Care Unit (ICU) ventilator care in certain jurisdictions, which fat activists classified as eugenics. At the same time, in some jurisdictions, vaccination campaigns prioritized people with higher BMIs for scarcely available Covid vaccinations, also on the basis of fat bodies’ higher risk status for Covid death. This paper explores the seeming tension between two articulations of fat during the Covid pandemic, whereby fat bodies were simultaneously worthy of life and of death in the same moment. Using MBembe’s conceptualization of necropolitics, which draws out and expands upon Foucault’s notion of biopolitics, I argue that the two perspectives on fatness operated in tandem, within an overall temporal shift in classification of obesity: from that of a risk factor for eventual death to that of an emergent threat. Such a temporal shift, I argue, relied on well-worn eugenic patterns in Canada, through which “normative” white bodies were prioritized for life through a complex necropolitical practice by which fat bodies were both made live and let die.